Lujo y alteridad: el exceso como salvoconducto para evadir/seducir al Otro. Acercamiento a los filmes The Bling Ring (2013) de Sofia Coppola, Les derniers jours du monde (2009) de Arnaud y Jean-Marie Larrieu, y The Great Gatsby (2013) de Baz Luhrmann - Mauricio Díaz Calderón (Études Caribéennes)
In current consumer societies, cinematography plays a privileged role as a spreading vehicle. So, it is relevant to recognize how films build their messages and fix in the social imaginary. The The Bling Ring film (2013), by American Sofia Coppola; Les Derniers Jours du monde (2009), by French brothers Arnaud and Jean -Marie Larrieu; and The Great Gatsby (2013), by Australian Baz Luhrmann, have in common the exploration of a luxurious and ostentatious world. The analysis focusses on certain text passages, allowing the identification of constituent elements, visual strategies and social values ​​used by these three films in the representation of the overabundance field. Despite the diversity of cultural contexts, the goal is to recognize textual affinities on exposing these exclusive spaces, and to point out the expressed symbolic and social concerns.